Treatment of prolonged clonidine-induced autonomic instability with midodrine: a case report about a new approach or a cautionary tale? - Saada Malouf; Catherine Henry; Lara Pemberton; Joe-Anthony Rotella (Emergency and Critical Care Medicine)
Abstract. Background. Clonidine is a centrally acting α2 adrenergic and imidazoline-1 receptor agonist that can cause somnolence, bradycardia, and hypotension within several hours of ingestion. Less well-described but observed by us locally is the observation that patients presenting after large overdoses including clonidine can have prolonged autonomic instability. As a result, they may require many days in hospital before recovery. We have previously used midodrine as an indirect antagonist with good effect; however, there are no previous reports of its use for this indication. Case presentation. We present the case of a young female patient who developed prolonged autonomic instability following a large overdose of clonidine (coingested with smaller doses of escitalopram + lisdexamfetamine) that was treated with midodrine but complicated by a type 2 non-ST segment elevated myocardial infarction. Conclusion. Midodrine seems to ameliorate this protracted instability and may provide a means to decrease hospital length of stay in appropriate individuals.